The Overexpression of Acyl-CoA Medium-Chain Synthetase-3 (ACSM3) Suppresses the Ovarian Cancer Progression via the Inhibition of Integrin β1/AKT Signaling Pathway - Yan, Limei; He, Zeping; Li, Wei; Liu, Ning; Gao, Song (Frontiers in Oncology, 2021)
Ovarian cancer is considered one of the most fatal gynecologic malignancies. This work aimed to explore the effects and regulatory mechanism of Acyl-CoA medium-chain synthetase-3 (ACSM3, a subunit of CoA ligases) in ovarian cancer progression. As well as employing CCK-8 assay, clone formation assay and cell cycle analysis were carried out to investigate cell proliferation ability. Wound healing assay and transwell assay were subsequently used to assess cell migration and invasion. Mice xenografts were then conducted to measure the effects of ACSM3 on tumor development in vivo. Our bioinformatics analysis suggested that the expression of ACSM3 was down-regulated in ovarian cancer tissues, and the patients with low expression of ACSM3 showed poor overall survival. We artificially regulated the expression of ACSM3 to evaluate its effects on ovarian cancer malignant phenotypes. Our data revealed that the overexpression of ACSM3 inhibited cell proliferation, migration, and invasion of ovarian cancer cells. In contrast, the knock-down of ACSM3 received the opposite results. Our western blot results showed that the Integrin β1/AKT signaling pathway was negatively regulated by ACSM3 expression. Moreover, ACSM3 overexpression-induced suppression of cell migration and invasion activities were abolished by the overexpression of ITG β1 (Integrin β1). Additionally, the growth of ovarian cancer xenograft tumors was also repressed by the overexpression of ACSM3. And ACSM3 interference obtained the contrary effects in vivo. In summary, ACSM3 acts as a tumor suppressor gene and may be a potential therapeutic target of ovarian cancer.